Mellow Crunch Viral / Nurul Atikah Norman - Norman, Nurul Atikah (2021)
Mellow Crunch Viral offers a side dessert and snack chocolate-based product food and beverage to give the satisfaction of customers. It is already identifying based on my observation that the people in Malaysia love to eat chocolate and crunchy stuff as their snack and side dessert. It is affordable price of product. It is also targeting all ages, gender even marital status such as children, family and student to buy this Mellow Crunch product. Mellow Crunch Viral marketing strategy is to emphasize the product's quality and price It provides an affordable price because many people want to buy this product, particularly in rural areas like mine. As a result, I devise a marketing strategy that excites customers to purchase mellow crunch brand Hanifjamals or known as Anep. He is a good influencer who enjoys providing good advice to young people. Besides, the design of the product is really attracting to sell it. The flavor is delectable, and the product is of excellent quality. Lastly, I, Nurul Atikah Binti Norman, am also in charge of the Mellow Crunch viral. I created Facebook in order to expand my business through social media and to learn how to post teaser, soft sell, and hard sell Facebook posts for company products. I also need to get at least 91 likes on Mellow Crunch Viral Facebook page. Selling and promoting this as my own project is a challenge for me. So, in this report, I will present proof of the business, such as some of the items that have been posted on Facebook, as well as the business background.